Viability assessment of WPS 2.0 services as communication standard for expensive web-based machine learning analysis. A case of study : Indoor Location - Calia, Andrea (2016)
Dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geospatial Technologies